Prozostrodon brasiliensis, a probainognathian cynodont from the Late Triassic of Brazil: second record and improvements on its dental anatomy - Pacheco, Cristian P. (2018)
Probainognathian cynodonts are conspicuous elements of the Assemblage Zones of the Triassic Santa Maria Supersequence in southern Brazil. Within this group, the derived clade Prozostrodontia, in which the crown group Mammalia is included, is taxonomic diverse in the Hyperodapedon and Riograndia AZs. We describe here the second known specimen (CAPPA/UFSM 0123) of Prozostrodon brasiliensis, until now only represented by its holotype. CAPPA/UFSM 0123 includes a right dentary with dentition. As in the holotype of P. brasiliensis, it has four lower incisors, pc4 with conspicuous cusp a, and small cusps b, c, and d, pc5-pc6 of ‘triconodont’ type with cusps a > c > b > d, with continuous lingual cingulum bearing up to six small discrete cusps, length of the lower tooth row more than half the length of the dentary, and relatively deep horizontal ramus of the dentary. The new specimen is about 25% smaller than the holotype and there is not a diastema between the canine and postcanine teeth, indicating its juvenile condition. Based on both known specimens of P. brasiliensis, a discussion on tooth replacement is presented, showing that the adult individual has more postcanine tooth morphotypes than the juvenile one.